Teaching Sustainability in Higher Education: Pedagogical Styles that Make a Difference - Scarff Seatter, Carol; Ceulemans, Kim (Canadian Journal of Higher Education, 2017)
The challenge of teaching sustainable development in higher education can mean that students—as future citizens—are left without insight, commitment, or a sense of their position regarding meaningful beliefs and actions related to sustainability. A paradox arises when educators approach a sustainability curriculum that has the potential to transform students’ thinking and actions, with a reductive and non-substantive pedagogy. This paper uses an epistemological and pedagogical analysis of relevant literature to redefine, clarify, and provide a more systematic and holistic understanding of a transformative pedagogy required for learning. The central thesis juxtaposes three sustainability curricular positions with three pedagogical models that vary decidedly in their emphasis on the prerogative of the learner’s prior knowledge and beliefs, the engagement of the learner, and the potential for critical thinking and transformative learning. It is found that a transformative pedagogy overcomes and eliminates the paradox, helping societies become more sustainable.